Baseline immunity predicts prognosis of pancreatic cancer patients treated with WT1 and/or MUC1 peptide-loaded dendritic cell vaccination and a standard chemotherapy. Issue 12 (2nd December 2021) - Ota, Shuichi; Miyashita, Mamiko; Yamagishi, Yuka; Ogasawara, Masahiro
ABSTRACT: The prognosis of patients with advanced pancreatic cancer is poor despite the recent introduction of immune checkpoint inhibitors. Therefore, the development of new therapeutic approaches is urgently required. In the present phase I/II study, we have evaluated the safety, the efficacy and the prognostic factors of Wilms' tumor 1 (WT1) and/or mucin 1 (MUC1) peptide-loaded dendritic cell (DC) vaccination in combination with a chemotherapy employing gemcitabine plus nab-paclitaxel or a combination chemotherapy regimen consisting of oxaliplatin, irinotecan, fluorouracil and leucovorin (FOLFIRINOX) in patients with advanced or relapsed pancreatic ductal adenocarcinoma (PDAC). Forty-eight eligible patients were enrolled and received the vaccinations approximately every 2–4 weeks at least seven times. No severe adverse events related to the vaccinations were observed. Median progression free survival and overall survival were 8.1 months and 15.1 months, respectively. DC vaccinations augmented tumor specific immunity which might be related to clinical outcome. The multivariate analyses demonstrated that WT1 or MUC1-specific interferonɤ enzyme-linked immunospot number prior to DC vaccination was an independent prognostic factor related to overall survival. These results indicate that DC-based immunotherapy combined with a conventional chemotherapy is safe and has clinical benefits for patients in advanced stage of PDAC. The precise evaluation of the baseline antitumor specific immunity is critical to predict clinical outcome.